PECULIARITIES OF THE FORMATION AND DEVELOPMENT OF HIGHER EDUCATION IN THE UNITED STATES OF AMERICA - ПЛАХОТНІК, Ольга (Київський національний університет імені Тараса Шевченка, 2025)
Background. The development of higher education in the United States has rather long history. Socio-political concepts that were determined by the scientific and technical revolution, the formation of pluralistic democracy, globalization, and the construction of a technocratic society played a decisive role in the history of the development of higher education in the United States of America. Scientific studies of famous American scientists D. Bock, M. Berry, V. Janes, L. Gordon, J. Edwards, T. Deer, J. Duderstadt, J. Gatto etc related to the study of issues of the Revolutionary War and its influence on American education; education of women, Native Americans, Latinos, and Asian Americans; the impact of the Great Depression, the Second World War and the Cold War on American education; a lot of attention was paid to the formation and development of public universities in the United States of America, as well as issues related to the democracy and accessibility of education, racial and ethnic discrimination, and are gaining relevance in the context of the creation of virtual universities and the narrow professionalization of specialists. Results. The university became an indicator that revealed and continues to reveal all the contradictory social consequences of social changes. It led to political discussions between conservatives and liberals about the state's policy in higher education, about the goals and social responsibility of higher education, and contributed to the development of new concepts of technocratism and the information society on the other hand. The development of education in general and higher education in the United States in particular was significantly influenced by religious doctrine and the church, which were decisive, despite the democratic character of American society. After all, the first colleges were created and functioned as religious ones. The analysis of historical-pedagogical, scientific-pedagogical and political literature gives ground for the statement that the US higher education system has a diversified structure and interesting traditions of forms and methods of education. Many achievements of the American higher school in the field of technical sciences and in the organization of the educational process are indisputable. Conclus і ons. The integration of the system of domestic higher education into the global educational space is one of the priority tasks of today, which requires appropriate consideration of the general trends of world development in the process of transformation and modernization of our system of domestic higher education, there is a need to study and generalize the positive foreign experience of the development of higher education.

Вступ . Розвиток вищої школи США має досить тривалу історію. Соціально-політичні концепції, які були обумовлені науково-технічною революцією, становленням плюралістичної демократії, глобалізацією, побудовою технократичного суспільства відігравали визначальну роль у історії розвитку вищої освіти у Сполучених Штатах Америки. Наукові дослідження відомих американських учених Д. Бока, М. Беррі, В. Джейнса, Л. Гордона, Дж. Едвардса, Т. Діра, Дж. Дудерштадта, Дж. Гатто й ін. пов'язані з вивченням питань Війни за незалежність і її вплив на американську освіту; освіти жінок, корінних американців, латиноамериканців і американців азійського походження; вплив Великої депресії, Другої світової та холодної воєн на американську освіту; чимало уваги приділяли становленню й розвитку державних університетів Сполучених Штатів Америки, а також питань, пов'язаних із демократичністю й доступністю освіти, расовою й етнічною дискримінацією та набувають актуальності в умовах створення віртуальних університетів і вузької професіоналізації фахівців. Результати . Університет став індикатором, що виявляв і продовжує виявляти всі суперечливі соціальні наслідки суспільних змін. Це призводило до політичних дискусій між консерваторами та лібералами про політику державивідносно вищої освіти, про цілі й соціальну відповідальність вищої школи і сприяло розвитку нових концепцій технократизму й інформаційного суспільства з іншого боку. На розвиток освіти загалом і вищої освіти США зокрема, значний вплив мала релігійна доктрина й церква, які були визначальними, незважаючи на демократичний характер американського суспільства. Адже перші коледжі створювалися та функціонували як релігійні. Аналіз історико-педагогічної, науково-педагогічної й політичної літератури дає підстави до твердження, що система вищої освіти США має диверсифіковану структуру та цікаві традиції форм і методів навчання. Незаперечними є багато досягнень американської вищої школи в галузі технічних наук, в організації освітнього процесу. Висновки . Інтеграція вітчизняної системи вищої освіти у світовий освітній простір є одним із пріоритетнихзавдань сьогодення, що потребує відповідного врахування загальних тенденцій світового розвитку у процесі трансформації й модернізації нашої вітчизняної системи вищої освіти, є потреба у вивченні й узагальненні позитивного зарубіжного досвіду розвитку вищої школи.
ОСОБЛИВОСТІ СТАНОВЛЕННЯ Й РОЗВИТКУ ВИЩОЇ ОСВІТИ У СПОЛУЧЕНИХ ШТАТАХ АМЕРИКИ
Keywords: становлення й розвиток освіти Сполучених Штатів Америки; наукові дослідження; університети Ліги плюща; заснування державних університетів.